NEPHROPROTECTIVE AND DIURETIC EFFECT OF NIGELLA SATIVA L SEEDS OIL ON LITHIASIC WISTAR RATS - Benhelima, Abdelkader; Kaid-Omar, Zohra; Hemida, Houari; Benmahdi, Tarek; Addou, Ahmed (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background and objective: The purpose of the current investigation was to study the influences, preventive and diuretic, of Nigella sativa L. seeds oil (NSSO) on calcium oxalate (CaOx) urolithiasis induced in Wistar male rats. Methodology: Seeds of Nigella sativa L. (N.S) were analysed for the evaluation of the concentration of oxalate and calcium. Nigella sativa L. seeds oil is obtained by hydrodistillation and HPTLC densitometric method was adopted to determine the amount of thymoquinone (TQ) present. Thirty male Wistar rats were divided into 5 groups (N=6). Group I, negative control, drank tap water. The other groups were II Positive control, III, IV and V received a treatment model inducing calcium oxalate urolithiasis for 28 days, using an aqueous solution involve 0.75% (EG) ethylene glycol and 1.0 % (AC) chloride ammonium. Rats in group III received in addition, 750 mg/kg Cystone from the beginning to the end of calculi induction experimentation. However, rats in Groups IV and V received (NSSO) at 5 ml/kg b.w by gavage on days 1st to 28th and 15th to 28th days, respectively. On days 0, 7, 14, 21 and 28, body weights were measured and the 24-hour urine samples were accumulated and analysed for biochemical elements. On the 28th day, blood samples were collected for the estimation of serum parameters including creatinine, BUN and uric acid. All animals were sacrificed at the end of the experiment and the kidneys were detached for histopathological examination. Results: Administration of (NSSO) at 5 ml/kg body weight/dose/day for 28 days exerts a protective effect by reducing significantly (p <0.01) urinary and serum rates of calcium, phosphate and oxalate. This preventive diet could increase the volume of urine excreted. Conclusion: The nephroprotectrice and diuretic activity demonstrated by Nigella sativa L. gives a scientific basis that approves their traditional use like a remedy against urolithiasis.